Velocity loss in sprint with resisted sled in highly competitive young female soccer players - Cofré Bolados, Cristian; Duarte Meneses, Sergio; Cursach, John; Vidal Díaz, Félix; Farias Valenzuela, Claudio; Rojas Trelles, Loreto; Torres, Hernán; Fuentes, Adolfo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The literature presents a variety of methods to improve acceleration speed, such as resisted sled sprint training. The aim of this study was to describe the behavior of time, speed, and speed loss when executing accelerations in 20 meters without load and with a resistance sled with loads equivalent to 8%, 12%, and 15% of body weight. It corresponded to a descriptive cross-sectional study. A repeated measures ANOVA analysis was performed for the four conditions: acceleration race without resistance; with 8% of body weight; 12% of body weight; and 15% of body weight in time in seconds to travel the first 10 meters; the 10 to 20 meter section; and the entire distance from 0 to 20 meters; speed in km/h to travel from 0 to 10 meters; from 10 to 20 meters; and from 0 to 20 meters; speed loss with different loads, contrasted with running without resistance; from 0 to 10 meters; from 10 to 20 meters; and from 0 to 20 meters. The sled training showed limited speed losses with very light resistances of 8%, while light resistances of 12% and 15% produced significant losses over the average speed, exceeding the threshold that affected the kinetics and kinematics of the acceleration race.